2009
DOI: 10.1007/s12010-009-8872-9
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Screening of Microorganisms for R-(+)-Limonene and (−)-β-Pinene Biotransformation

Abstract: This work is focused on the biotransformation of R-(+)-limonene and (-)-beta-pinene to bioflavor production. To carry out the present study, 405 microorganisms were tested for their ability to bioconvert the substrates. From the isolated microorganisms, 193 were selected in the prescreening using mineral medium for limonene degradation. At the screening step, eight strains were able to convert R-(+)-limonene and 15 to transform (-)-beta-pinene, both in alpha-terpineol. The highest concentration in alpha-terpin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 28 publications
0
12
0
2
Order By: Relevance
“…and yeasts previously isolated by our research group using the methodology of experimental design. Additionally, comparing the results obtained here with that published previously [14], here, we have tested different newly isolated microorganisms whereas in the other work, only microorganisms identified and easily available (ATCC) were used. Additionally, in the present study, a systematic study was carried out by means of using of a well-recognized tool (experimental design).…”
Section: Introductionmentioning
confidence: 87%
“…and yeasts previously isolated by our research group using the methodology of experimental design. Additionally, comparing the results obtained here with that published previously [14], here, we have tested different newly isolated microorganisms whereas in the other work, only microorganisms identified and easily available (ATCC) were used. Additionally, in the present study, a systematic study was carried out by means of using of a well-recognized tool (experimental design).…”
Section: Introductionmentioning
confidence: 87%
“…In addition, this trait is easy to measure and has been widely used in screening and selection assays among strains with different ploidy states (Bicas and Pastore, 2007;Clark and Anderson, 2004;Eichlerova and Homolka, 1999;Hiscox et al, 2010;Rottava et al, 2010).…”
Section: Pre-screening Experiments: Analysis Of Mycelium Growth Ratesmentioning
confidence: 99%
“…The results showed that (i) a few isolates from PSA-69 and PSA-224 grown on SNL medium reached a similar growth rate as the corresponding parental Dk, and (ii) most of the Mks grown on SNL-Val showed a similar or higher growth rate than their corresponding parental Dk, proving that it was possible to obtain better adapted phenotypes able to colonize a selective medium faster. The good performance obtained by each set of Mks on SNL-Val can be explained by the great flexibility of metabolic processes and enzymes involved enabling a saprobic cell to feed on complex organic molecules in variable environments (Rottava et al, 2010). This fact highlighted the need to compare the development of fungi in different environments, because fungal strains react differently to a stimulus by the medium composition.…”
Section: Monokaryons Screening Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, microorganisms from culture collection are screened on their ability to transform the molecule of interest [6][7][8][9][10] or after a prescreening based on culture conditions of microorganisms obtained from environment [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%